The Effect of Intellectual Capital on Financial Statement Fraud in Manufacturing Companies Listed on Indonesia Stock Exchange 2018-2022 - Nurul Qalbi Awaliyah; Siti Mutmainah (Jurnal Akuntansi dan Perpajakan, 2023)
Financial statement fraud is the rarest but most detrimental fraud. This type of fraud is growing and becoming more complicated than before due to technological developments. The massive use of technology increases dependence on intellectual assets so that these assets are predicted to minimize the potential for financial statement fraud. This study aims to examine whether intellectual capital negatively affects the probability of financial statement fraud. 105 observations from 30 manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022 were sampled through purposive sampling techniques. Data was analyzed using descriptive statistics and panel data analysis processed with Eviews version 12. The results showed that only relational capital had an effect in reducing the possibility of financial statement fraud while structural capital had no effect. Human capital is known to be able to increase the possibility of financial statement fraud. This findings contributes to the need to consider intellectual capital in investigating financial statement fraud and other type of fraud.